Factores Motivacionales Que Interfieren en el Desarrollo Del Trabajo De Grado En 5 Egresados de La Facultad De Psicologia En La Universidad Antonio Nariño (2015)
The objective of this work is to analyze the motivational factors that interfere in the development of the degree work of five graduates of the Antonio University Narino. The methodology is qualitative of a descriptive type and for this study, use was made of the interview as a means of data collection. As a result of this study, identify the motivational factors that most influence the development of the work of degree, taking as evidence the experiences of each of the graduates participants, and relating their experiences in the course of carrying out their work degree. In conclusion, it is obtained that two specific factors, the motivation factor of achievement and the motivation factor of expectations, are the ones that most interfere with the work of students when they do their degree work. It is also established that the main The objective expressed by the graduates regarding the development of their degree work is finally achieve graduation, above the purposes of learning from their research.